The Position of The People’s Representative Council in the Indonesian Constitutional System - Rochmwanto, Munif; Isnaini, Enik; Hadinata, Candra Tirta (Jurnal Independent, 2025)
ABSTRACT This research is based on the fact that Indonesia is a country based on law as regulated in Article 1 Paragraph (3) of the 1945 Constitution. One of the principles of the State of Law is the guarantee of human rights. As a country with people's sovereignty, the state guarantees the rights of citizens, including freedom of expression in public. This research method uses a normative legal research type, with a legislative approach and a conceptual approach. From the results of the study, it can be concluded that from the perspective of a state based on law, freedom of expression in public is a constitutional right of every Indonesian citizen and as a guarantee of protection of human rights, so that its existence is guaranteed by law. Meanwhile, from the perspective of a democratic state, freedom of expression is a form of people's sovereignty, where the people must get broad participation space in determining government policies. Therefore, the law guarantees people's freedom as a form of people's sovereignty, but the way people's aspirations are conveyed must be based on legal provisions.